Assessment of compressive strength of historic mixed masonry - Witzany, Jiří; Čejka, Tomáš; Sýkora, Miroslav; Holický, Milan (Journal of Civil Engineering and Management, 2016)
The majority of load-bearing masonry structures of historic buildings are built of mixed or stone masonry composed of regular or irregular (so-called quarry) masonry units – bricks, sedimentary and metamorphic rock – possessing often very different physical and mechanical characteristics. The identification of residual mechanical properties of stone or mixed masonry of irregular walling units requires the application of a suitable diagnostic method, the assessment of the phase of degradation processes and the choice of an appropriate probabilistic model for the strength of mixed masonry. The presented experimental research involves the analysis of the heterogeneity (homogeneity) of mixed masonry of a church from the 17th century. The probabilistic model for masonry strength is developed on the basis of destructive and non-destructive testing of masonry units and mortar. It appears that the probabilistic approach leads to a design value by 75% higher than the deterministic approach.First published online: 14 Sep 2015